Notes on the notion of dialectics in Fanon - Giangrande, Matteo (Itinerari, 2023)
The article examines the notion of dialectics in Fanon’s thought, analyzing its use first in Peau noire masques blancs, later in political writings, and finally in Les damnés de la terre. It will show how “dialectic” in Fanon refers to three distinct spheres. The first concerns dialectic as a transdisciplinary method of investigation; we will see its application both to psychiatry as a sociogenetic perspective of the pathological interaction between the ego and the world, and to social reality as an analysis of its contradictions. The second concerns the impossibility of triggering the Hegelian dialectic of mutual recognition in colonial relations. The third focuses on dialectics as a contradictory historical process. Analyzing the phases of colonization and decolonization, we will illustrate the Fanonian critique of the objective view of historical dynamics, emphasizing the transformative and strategic capacity of interacting subjectivities.